Fostering Interprofessional Patient-centred Collaboration in Healthcare through CPD: Our Learnings from the PARTNER Programme. Issue 1 (1st January 2020) - Wei Qi, Loh; Barclay, Audra; Garcia, Tina; Sullivan, Lisa
ABSTRACT: Interprofessional patient-centred collaboration in healthcare is necessary for the effective management of chronic diseases. Continuing professional development (CPD) programmes that offer a platform for healthcare professionals of different disciplines to convene and learn together may function as an effective platform to both foster greater collaboration between them and increase awareness of patient perspectives. We report on our learnings from organising the PARTNER programme – a CPD initiative on the management of psoriasis and/or psoriatic arthritis – that targeted both specialists (comprising rheumatologists and dermatologists) and primary care. After participating in the programme, learners demonstrated a stronger intent to collaborate with each other and a heightened awareness of patient perspectives. However, changes at a practice level could not be evaluated due to the lack of substantial follow-up data. Our experience offers useful insights as to the effectiveness and limitations of organising CPD programmes to promote interprofessional collaboration and patient-centred care. The role of such programmes in the management of chronic diseases, and their ideal format, should be further explored as they have potential to effect change in practice.